2005
DOI: 10.1152/ajpregu.00149.2004
|View full text |Cite
|
Sign up to set email alerts
|

Chronic alterations in ovine maternal corticosteroid levels influence uterine blood flow and placental and fetal growth

Abstract: Previous work from this laboratory demonstrated that the elevation of maternal plasma corticosteroid concentrations during pregnancy is important for the support of fetal development. Reducing ovine maternal plasma cortisol concentrations to nonpregnant levels stimulates homeostatic responses that defend fetal blood volume. The present study was designed to test the hypothesis that chronic decreases or increases in maternal plasma cortisol concentration alter uterine and placental blood flow and morphology. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 35 publications
8
71
1
1
Order By: Relevance
“…We did not observe an increase in arterial pressure in response to the moderately elevated cortisol levels indicating that the fetal hearts in this study were not subjected to chronically increased systolic load, a possible trigger to myocyte hypertrophy seen in some other studies. Although in the present study blood pressure was only measured at 10 days of cortisol infusion, in our previous study (Jensen et al 2005) fetal arterial blood pressure was not elevated at either 5 or 10 days of maternal cortisol infusion. The doses of cortisol administered in our study resulted in relatively small increases in fetal cortisol, well below those that have been shown to increase fetal blood pressure in other studies (Wood et al 1987, Tangalakis et al 1992, Unno et al 1999.…”
Section: Mechanisms Of Enlargement Of the Fetal Heartcontrasting
confidence: 54%
See 2 more Smart Citations
“…We did not observe an increase in arterial pressure in response to the moderately elevated cortisol levels indicating that the fetal hearts in this study were not subjected to chronically increased systolic load, a possible trigger to myocyte hypertrophy seen in some other studies. Although in the present study blood pressure was only measured at 10 days of cortisol infusion, in our previous study (Jensen et al 2005) fetal arterial blood pressure was not elevated at either 5 or 10 days of maternal cortisol infusion. The doses of cortisol administered in our study resulted in relatively small increases in fetal cortisol, well below those that have been shown to increase fetal blood pressure in other studies (Wood et al 1987, Tangalakis et al 1992, Unno et al 1999.…”
Section: Mechanisms Of Enlargement Of the Fetal Heartcontrasting
confidence: 54%
“…The cortisol dose and the duration of cortisol infusion (10 days) were determined based on a previous study in this laboratory (Jensen et al 2005) showing that infusion at this rate and duration produces levels similar to mild maternal stressors and results in enlargement of the fetal heart.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The observations of Caton et al [ 2 5 ] s u g g e s t t h a t e s t r o n e , e s t r a d i o l a n d progesterone have some effect on the rate of uterine blood flow. Recently, Jensen et al [26] reported that maintenance of increased cortisol concentrations during pregnancy was essential for the normal gestational increase in uterine blood flow in ewes and that even small reductions in maternal cortisol levels resulted in on altered placental structure and slowing of fetal growth. Unfortunately, we found statistically that neither gravid nor nongravid UBF decreased as gestation progressed to parturition.…”
Section: Discussionmentioning
confidence: 99%
“…As such, numerous effects beneficial to pregnancy have already been attributed to aldosterone. These include, but are not limited to maternal plasma volume expansion, improved fetal conditions and size, placental growth and lower maternal blood pressure (2)(3)(4)(5)(6)(7)(8). We recently described that vascular endothelial growth factor (VEGF) alone and in combination with angiotensin II, directs augmented aldosterone production in pregnancy (9), suggesting a physiological survival benefit.…”
Section: Introductionmentioning
confidence: 99%